Learning Towards an Ideal Education Through Social Studies Learning Tools in Jombang Regency - Prastuti, Ajeng Eka; Sarmini, Sarmini; Purnomo, Nugroho Hari (International Journal for Educational and Vocational Studies, 2020)
Education as a process of learning and channeling knowledge, changing behavior and shaping personal character must be done well. Teachers have an important influence on the keys to success and success of the learning process based on national education goals. In learning, an ideal set of learning tools is needed so that students are able to understand the material being taught well. Ideal education as the suitability that is aspired, expected and desired. The ideal learning process through learning tools is characterized by the nature of students becoming active. This research method uses content analysis, descriptive research types and qualitative approaches. The results of the study, from 10 schools that were sampled as many as 6 schools with complete categories that have a match between 8-11 components and 4 schools have a very complete category that has a compatibility between 12-13 components.